2019
DOI: 10.1111/1541-4337.12482
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Stability Mechanism and Application of Water‐in‐Oil Emulsions Encapsulating Various Additives

Abstract: Water‐in‐oil (W/O) emulsions can be used to encapsulate and control the release of bioactive compounds for nutrition fortification in fat‐based food products. However, long‐term stabilization of W/O emulsions remains a challenging task in food science and thereby limits their potential application in the food industry. To develop high‐quality emulsion‐based food products, it is essential to better understand the factors that affect the emulsions’ stability. In real food system, the stability situation of W/O e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 152 publications
(179 reference statements)
1
89
0
Order By: Relevance
“…Another technique used to assess stability is Turbiscan Lab R Expert where it is possible to access the evolution of sample creaming by change in emulsion opacity under the Earth's gravity (Liu et al, 2011). The researchers interested in emulsion stability fundamentals and practices are advised to read Goralchuk, Grinchenko, Riabets, and Kotlyar (2019) and Zhu et al (2019), Karthik, Ezhilarasi, and Anandharamakrishnan (2017), among others.…”
Section: Stability Of Nanoemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another technique used to assess stability is Turbiscan Lab R Expert where it is possible to access the evolution of sample creaming by change in emulsion opacity under the Earth's gravity (Liu et al, 2011). The researchers interested in emulsion stability fundamentals and practices are advised to read Goralchuk, Grinchenko, Riabets, and Kotlyar (2019) and Zhu et al (2019), Karthik, Ezhilarasi, and Anandharamakrishnan (2017), among others.…”
Section: Stability Of Nanoemulsionsmentioning
confidence: 99%
“…In this context, this review offers an outline of the recent scientific contributions aiming for the application of natural emulsifiers for NE production and assesses their prospective appliance in the food industry, based on papers published from 1993 to 2020, and with focus on O/W NEs. This type of NE has a greater potential for application in foods, as they are normally aqueous systems, whereas W/O NEs would be more suitable for fat-based food products, which means that it has a more restricted application (Porras, Solans, González, & Gutiérrez, 2008;Zhu et al, 2019). This review approached natural emulsifiers, selection of emulsifiers, selection of homogenization techniques, formation of NEs, stability of NEs, and application of NEs.…”
Section: Introductionmentioning
confidence: 99%
“…The emulsifier composition (v/v) was S80/T80 at 54/46 (HLB 9.2) and 80/20 ratios (HLB 6.4), and S85/T80 at 80/20 ratio (HLB 4.4), coded as S80/T80 54/46, S80/T80 80/20 and S85/T80 80/20, respectively. The chosen HLB range (4)(5)(6)(7)(8)(9), which in the classical HLB scale covers W/O and wettability agents, was chosen to be further experimentally validated as effective stabilizers for W/O systems. The used content of emulsifier was 6% (total emulsion-basis, v/v (%)).…”
Section: Systematic Study and Base Emulsion Selectionmentioning
confidence: 99%
“…W/O emulsions have high potential for cosmetic, pharmaceutical, agricultural, and food industries [3,[5][6][7]. For example, this type of emulsion can be used for the encapsulation of medicines, immobilizing enzymes, and loading protein drugs [5,8,9]. Its structure is suitable for the delivery of hydrophilic compounds, which, in turn, may bring different functions to the emulsified system, such as antimicrobial and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the water content and yield of tofu were decreased, whereas the protein, hardness, and crude fat were increased with increased MC in the W/O emulsion. The optimized microstructure and WHC of tofu were obtained when the concentration of MC in the W/O emulsion was 2.0 M. Other studies (Zhu et al, 2015;Zhu, Pan, et al, 2019) also reported that W/O emulsions showed good controlled release of Mg 2+ , which slowed down the aggregation speed of soy protein molecules. Compared with traditional MC, the use of W/O emulsions could significantly slow down the gelation rate of tofu products, thereby increasing its yield and improving its texture.…”
Section: Use Of Various Mixed Coagulantsmentioning
confidence: 78%